2006
DOI: 10.1007/s00436-006-0227-7
|View full text |Cite
|
Sign up to set email alerts
|

Anisakid parasites of two forkbeards (Phycis blennoides and Phycis phycis) from the eastern Mediterranean coasts in Tunisia

Abstract: Two gadiform species with a successive bathymetric and an ecological and economical importance in the Mediterranean fishing industry, Phycis blennoides and Phycis phycis, were selected for the present study. A total of 592 fresh specimens belonging to the Gadiformes genus were obtained from local commercial fisheries. The investigation was centred on anisakid parasites of 272 specimens of the greater forkbeard (P. blennoides) and 320 of the forkbeard (P. phycis) captured off the Mediterranean coasts of Tunisia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 13 publications
(20 reference statements)
0
18
0
Order By: Relevance
“…More generally, the 15°C summer isotherm has moved 330 km north in the last 17 yr (McMahon & Hays 2006), and studies by Beaugrand et al (2008) in the North Atlantic showed that regions in which biome boundaries shifts occur are more vulnerable to the impact of climate change. There is a general tendency for parasitic infections to increase with temperature (Farjallah et al 2006), and rising water temperatures have been reported to directly influence the incidence of disease threats from parasitic infections (Harvell et al 1999, Hakalahti et al 2006, particularly in temperate regions where transmission is strongly related to 'windows' of suitable temperature ranges. Increased infection pressure (as has apparently occurred with salmon) due to warming waters has been reported for metazoans (Argulus coregoni and Diplostomum spathacum usually found in fish culture) in Finland (Hakalahti et al 2006).…”
Section: Asp Ay821749 Tc--cgta Ta-cagttt--gtgtgatc-tatgt--caa Cgcaamentioning
confidence: 99%
“…More generally, the 15°C summer isotherm has moved 330 km north in the last 17 yr (McMahon & Hays 2006), and studies by Beaugrand et al (2008) in the North Atlantic showed that regions in which biome boundaries shifts occur are more vulnerable to the impact of climate change. There is a general tendency for parasitic infections to increase with temperature (Farjallah et al 2006), and rising water temperatures have been reported to directly influence the incidence of disease threats from parasitic infections (Harvell et al 1999, Hakalahti et al 2006, particularly in temperate regions where transmission is strongly related to 'windows' of suitable temperature ranges. Increased infection pressure (as has apparently occurred with salmon) due to warming waters has been reported for metazoans (Argulus coregoni and Diplostomum spathacum usually found in fish culture) in Finland (Hakalahti et al 2006).…”
Section: Asp Ay821749 Tc--cgta Ta-cagttt--gtgtgatc-tatgt--caa Cgcaamentioning
confidence: 99%
“…the number of hosts infected with one or more individuals of a particular parasite species, Bush et al, 1997) of larval anisakids can be very high (Chou et al, 2010). In some northern hemi-.......... sphere fisheries the prevalence has increased in recent years, enlarging the concern for human health and having adverse financial effects (Farjallah et al, 2006;Cabrera, 2010). There is an extensive world literature on Anisakis and anisakiosis.…”
Section: Introductionmentioning
confidence: 99%
“…as results of an interspecific hybridation between the two species of the A. simplex complex (Abollo et al 2003). The genus Anisakis was previously reported infecting some fish species from the North African coasts of central Mediterranean Sea (Farjallah et al 2006), although there are no studies that document distribution of the Anisakis larvae at species level in this area. The aim of the present work was to investigate, using RFLP genetic analysis and the molecular keys devised by D' Amelio et al (2000) implemented by Pontes et al (2005), the occurrence of larval forms of Anisakis spp.…”
Section: Introductionmentioning
confidence: 99%